Optimal management of renal cell carcinoma in octogenarians: Retrospective analysis using updated Korean Renal Cell Carcinoma (KORCC) database - Jung Kwon Kim; Gyoohwan Jung; Cheol Kwak; Chang Wook Jeong; Seok Ho Kang; Sung-Hoo Hong; Yong-June Kim; Jinsoo Chung; Eu Chang Hwang; Tae Gyun Kwon; Seok-Soo Byun (PLoS ONE, 2023)
Background There is few of optimal management guideline in elderly patients with renal cell carcinoma (RCC). To compare the survival outcomes of octogenarian RCC group and younger RCC group after surgery using nationwide multi-institutional database. Methods A total of 10,068 patients who underwent surgery for RCC were included in the current retrospective, multi-institutional study. A propensity score matching (PSM) analysis was conducted to control other confounding factors in analyzing survival outcomes of octogenarian and younger group RCCs. Kaplan-Meier curve analysis to calculate the survival estimates for cancer-specific survival (CSS) and overall survival (OS), and multivariate Cox-proportional hazard regression analyses to evaluate the significant variables associated with the survival outcomes were also performed. Results Both groups were well-balanced in all baseline characteristics. In a total cohort, Kaplan-Meier survival analysis showed a significantly decreased 5-year and 8-year CSS and OS in the octogenarian group compared with the younger group. However, in a PSM cohort, no significant differences were evident between the two groups in terms of CSS (5-year, 87.3% vs. 87.0%; 8-year, 82.2% vs. 78.9%, respectively, log-rank test, p = 0.964). In addition, age ≥ 80 years (HR, 1.199; 95% CI, 0.497–2.896, p = 0.686) was not a significant prognostic factor of CSS in a PSM cohort. Conclusions The octogenarian RCC group after surgery had comparable survival outcomes compared with younger group after PSM analysis. For the life expectancy of octogenarian is getting longer, active treatment is considerable in patients with good performance status.